2012
DOI: 10.1007/s00167-012-2284-z
|View full text |Cite
|
Sign up to set email alerts
|

Custom-fit minimally invasive total knee arthroplasty: effect on blood loss and early clinical outcomes

Abstract: Therapeutic study, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 37 publications
3
57
0
Order By: Relevance
“…Using both the KS and the OKS, we found no significant difference between PSCG and CI in terms of clinical results at three months. Other studies that have compared the short-term clinical results of PSCG and CI 23,31,32,35 have had similar outcomes to ours.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Using both the KS and the OKS, we found no significant difference between PSCG and CI in terms of clinical results at three months. Other studies that have compared the short-term clinical results of PSCG and CI 23,31,32,35 have had similar outcomes to ours.…”
Section: Discussionsupporting
confidence: 79%
“…6,7,22 Patient-specific instrumentation was introduced to translate 3D planning from the intra-operative to the pre-operative setting. To date, several controlled studies [13][14][15][16][17][23][24][25][26][27][28][29][30][31][32][33][34][35][36] have reported conflicting results from PSCG use in primary TKA (Table VI). In addition, both the 3D reconstruction of the knee computer algorithm and the block designs differ substantially from one system to another, which necessitates a specific evaluation of each PSCG system.…”
Section: Discussionmentioning
confidence: 99%
“…Abdel et al prospectively reviewed 20 patients who underwent MRI-based PSI surgery for three months and reported that the KSS, KOOS, SF-12 and 3-D gait parameters were no difference to conventional TKA [9]. Pietsch et al prospectively evaluated 40 patients who underwent MRI-based PSI surgery and concluded that the KSS was comparable to conventional TKA at three months post surgery [10]. Yaffe et al retrospectively studied 42 patients who underwent MRI-based PSI surgery.…”
Section: Score (Kss) and Western Ontario And Mcmaster Universities Armentioning
confidence: 99%
“…There is a paucity of published literature on the clinical outcomes after PSI surgery [7][8][9][10][11][12][13]. Furthermore, these studies are also limited by their short follow-up periods.…”
mentioning
confidence: 99%
“…However, even in the studies which report significantly shorter operative time, the time saved may not be sufficient to make enough theatre time available to allow further cases to be undertaken. 15,17,26,30 Surgeons vary significantly with regards to their surgical time even for CI TKR, (from 37.8 min to 128.1 min) with, predictably, the quicker surgeons reporting a mean surgical time of 44.3 min with PSG, which is still lower than most other studies. 17,32 It actually appears that quicker surgeons undertaking PSG may not reduce their surgical time, but for the majority the simplification of the operative steps should reduce the surgical time.…”
Section: Outliersmentioning
confidence: 85%